Argulosis causing juvenile mortality in some fishes at Kakdwip, West Bengal - Nandi, N C; Das, S R (Indian Journal of Fisheries, 2011)
Diseases and parasites of food fishes in India and adjacent countries were reported on several occasions (Gopalakrishnan 1967). A few cases of argulosis associated with fish mortality were also known from Indian ponds (Hora 1943; Anonymous 1955,1960; Gopalakrishnan 1963, 1964; Tripathi 1975). However, Ramakrishna (1951) reported the occurrence of Argulus siamensis for the first time from India. He had examined Southwell’s (1915) and Hora’s (1943) collection and identified them as A. siamensis. Afterwards areponof A. siamensis infecting large number of fishes of a pond at Salkia, Howrah, appeared in the Annual Report of the Central Marine Fisheries Research Institute, Mandapam (Anonymous 1955).